Cognitive development in pediatric epilepsy surgery - Ramantani, Georgia; Reuner, Gitta (Neuropediatrics, 2018)
Epilepsy surgery is a very effective treatment option for children and adolescents with drug-resistant structural epilepsy, resulting in seizure freedom in the majority of cases. Beyond seizure freedom, the postsurgical stabilization or even improvement of cognitive development constitutes a fundamental objective. This study aims to address key features of cognitive development in the context of pediatric epilepsy surgery. Many surgical candidates present with severe developmental delay and cognitive deficits prior to surgery. Recent studies support that global cognitive development remains stable after surgery. Individual developmental trajectories are determined by the degree of presurgical developmental impairment, age at surgery, seizure freedom, antiepileptic drug tapering, and other case-specific factors. Compared with adults, children may better compensate for temporary postsurgical deficits in circumscribed cognitive functions such as memory. Particularly for left-sided temporal resections, children present a clear advantage in terms of postsurgical recovery with regard to verbal learning compared with adults. In the case of severe presurgical developmental impairment, minimal postsurgical improvements are often not measurable, although they are evident to patients' families and have a large impact on their quality of life. Multicenter studies with a standardized assessment protocol and longer follow-up intervals are urgently called for to provide deeper insights into the cognitive development after epilepsy surgery, to analyze the interaction between different predictors, and to facilitate the selection of appropriate candidates as well as the counseling of families.
Published online December 5, 2017
Gesehen am 18.02.2019